Black‐hole attack and counter measure in ad hoc networks using traditional routing optimization. (2nd February 2023) - Pullagura, Joshua Reginald; Dhulipalla, Venkata Rao
Summary: Ad hoc networks have constraints like energy, memory, computation power, and communication range which makes the nodes vulnerable for attacks. In this article, black hole attack detection mechanism is carried out on traditional ad hoc on demand distance vector routing (AODV) protocol. Initially the proposed work proceeded with black‐hole attack configured on conventional AODV protocol. Black‐hole node will give route reply with highest sequence number to entice the sender to create a route through it. By using intruder detection system threshold mechanism, the black‐hole nodes are identified and isolated. In this article, maximal destination sequence number is estimated by using linear regression technique. Performance comparison is carried out with normal, black hole based and black hole detected routing mechanisms. The simulation findings show that that incorporated method enhances network performance by improving QoS under black hole attack.